ANALYSIS OF THE IMPLEMENTATION OF PROMOTIONAL STRATEGIES IN TOURISM DEVELOPMENT DURING THE COVID-19 PANDEMIC IN SERANG REGENCY: ANALISIS PENERAPAN STRATEGI PROMOSI DALAM PENGEMBANGAN PARIWISATA DI MASA PANDEMI COVID-19 DI KABUPATEN SERANG - Icin Quraysin (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2021)
The tourism sector is one of the factors that play an important role in Indonesia's economic growth and has the second largest foreign exchange contribution in Indonesia after foreign exchange from palm oil exports. Circular issued by the government on March 18, 2020, all indoor and outdoor activities in all sectors involved related to tourism and the creative economy was temporarily postponed in order to reduce the spread of the corona. Likewise, the tourism sector in Serang Regency, Banten, was temporarily paralyzed because there were no visitors coming, both local and foreign tourists, thus affecting people's income and also income. the area of ​​Serang Regency itself. The purpose of this study is to analyze the extent to which the implementation of promotional strategies applied by the Serang Regency Tourism and Creative Economy Office in tourism development in Serang Regency during the Covid-19 Pandemic and what policies should be implemented. This research was prepared by the Serang Banten Regency Government so that it can be used as a guide for stakeholders in the tourism world in Serang Banten Regency to jointly realize tourism recovery and be able to bring in large numbers of tourists during this COVID-19 pandemic. The research method used is qualitative descriptive method. Data collection was done by interview, direct observation, and documentation. Data analysis was carried out through data collection, data reduction, data presentation and drawing conclusions. the covid-19 pandemic, due to colliding with funds and human resources